Avaliação dos polimorfismos 14pb deleção/inserção e +3142 C/G da molécula do antígeno leucocitário humano G (HLA-G) em pacientes com hanseníase - Leotti, Naiana Fernandes (2010)
Leprosy is a chronic infection endemic in Brazil. The immune response to M. leprae is variable and may determine the evolution of the disease: predominance of Th1 immune response results in elimination of the bacteria or in the tuberculoid hanseniasis, whereas Th2 response is inefficient to eliminate it. HLA-G, an immunomodulatory molecule which has been recognized to mediate the inhibition of Th1 response, has two polymorphisms assigned in 3’UTR - a deletion/insertion of 14bp (14bp del/ins) and a base substitution in +3142 position (+3142 C/G) – which has been suggested influencing the expression levels of HLA-G. In this study, we evaluated the frequency of both polymorphisms in leprosy Brazilian patients (N= 162) compared with healthy controls (N=176). Moreover, the patients were stratified according to clinical features and co-infection with HBV and HCV, in order to verify a possible association of polymorphisms with these parameters. Genotyping was performed by PCR (14bp del/ins) and PCR-RFLP (+3142 C/G). No association between 14bp del/ins polymorphism with disease, clinical manifestations or presence of other infections was found. However, a higher frequency of individuals with genotype +3142C/C allele was observed in the patient group (p=0.03, OR=2.10, 95% CI=1.09-4.8). The frequency of +3142C allele was also increased in this group (p=0.048, OR=1.38, 95% CI=1.01-1.88). No association with clinical manifestations or presence of other infections was detected. Considering the negative effects of G allele on HLA-G expression, it is possible that the CC homozygous presents a higher HLA-G expression in comparison with GG homozygous, which may have unfavorable consequences to modulation of immune response to M. leprae. These obtained results suggest that polymorphism +3142 C/G may influence the susceptibility to M. leprae infection in Brazilian patients.